Perceived peer relationships and achievement motivation: Subject-specific dynamics in a Chinese high school learning context - Cui, Tianxue; Cheng, Emily Hongzhen; Shi, Jian; Liu, Qimeng (British journal of educational psychology, 2025)
This study employed a three-wave random intercept cross-lagged panel model (RI-CLPM) to investigate whether a reciprocal relationship exists between perceived peer relationships (intimacy and conflict) and achievement motivation in math and English in the Chinese context. A total of 4040 high school students were tracked with their perceived intimacy and conflict with peers and achievement motivation levels in math and English over three academic years since Grade 10. A reciprocal association was found between perceived peer intimacy and achievement motivation in English, and the predictive effect of intimacy on achievement motivation in English was the same as the reverse association. Only a unidirectional association between perceived peer intimacy and achievement motivation in math could be found. Perceived peer conflict change could not be significantly related to the change in achievement motivation in either math or English. This study emphasizes that the influence of peer intimacy on achievement motivation is more pronounced compared to that of peer conflict. Moreover, the effect of peer intimacy varies across subject areas. Notably, there is no need for motivational intervention approaches based on gender in math and English.